2019
DOI: 10.1089/acu.2019.1391
|View full text |Cite
|
Sign up to set email alerts
|

Using Forbidden Points in Pregnancy: Adverse Outcomes and Quality of Evidence in Randomized Controlled Trials—A Systematic Narrative Review

Abstract: Objective: Pregnancy is a complex physical and hormonal condition. Many women experience back and pelvic pain, reflux, and headaches during pregnancy. There has been a significant rise in the popularity of acupuncture for pain conditions in pregnancy, wherein nonpharmacologic options are important. Concerns have been raised by both traditional and medical acupuncturists about using ''forbidden points'' during pregnancy and the risk of preterm contractions (PTC), as this could limit women's and practitioners' w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…It also suggested that studies collect and report on safety outcomes for trials involving pregnancy women. 22 One previous review 23 reported the effectiveness of acupuncture in treating LBPP for pregnant and postpartum women. However, the number of studies associated with LBPP during the pregnancy included were small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also suggested that studies collect and report on safety outcomes for trials involving pregnancy women. 22 One previous review 23 reported the effectiveness of acupuncture in treating LBPP for pregnant and postpartum women. However, the number of studies associated with LBPP during the pregnancy included were small.…”
Section: Introductionmentioning
confidence: 99%
“…It was recommending that due to the concern of high dropout rates from studies that use forbidden points, alternative points should be considered in the treatment of LBPP, which have demonstrated effectiveness. It also suggested that studies collect and report on safety outcomes for trials involving pregnancy women 22. One previous review23 reported the effectiveness of acupuncture in treating LBPP for pregnant and postpartum women.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while it improved heartburn, it also reported no adverse effects other than one patient having ecchymosis at insertion points 192 . There have been concerns from acupuncturists regarding the risk of preterm contractions with acupuncture during pregnancy 193 . Nevertheless, when used correctly, acupuncture has been successfully and safely used for migraine during pregnancy and labour and back pain in pregnancy 194–196 .…”
Section: Management Of Pre‐existing Functional Dyspepsia In Pregnancymentioning
confidence: 99%
“…89 Generally, there are several acupoints that are "forbidden" before 37 weeks of gestation due to concerns about preterm contractions and there is a recent systematic review that confirms this view. 90 Several studies have investigated the safety of moxa use. They found that cardiotocograms were normal and there were no fetal side effects including, no fetal heart rate abnormalities, preterm uterine contractions, fetal distress, changes in short-term or long-term variability, or maternal cardiovascular changes.…”
Section: Side Effectsmentioning
confidence: 99%